Effect of irrigation levels at different growth stages on growth parameters and yield of four selected chilli accessions (Bangladesh Journal of Agricultural Research, 2010)
An experiment as conducted at Bangladesh Agricultural University. Mymensingh in poly bags under glasshouse condition during October 1997 to March 1998 to know the effects of different water levels at different growth stages of four selected chilli accessions viz., C-027l, C-0272, C-0275, and C-0277. Six water treatments viz., watering once everyday (W1), watering twice everyday (W2). watering at 4 days interval (W3), watering at 8 days interval (W4), watering at 16 days interval (W5), and no watering (W0) were tested at three growth stages viz., Vegetable stage (S1), Flowering stage (S2), and Fruiting stage (S3). The accessions of chilli were selected from the results of a previous experiment where ten accessions of chilli collected from Spices Research Centre (SRC) of Bangladesh Agricultural Research Institute, Joydebpur, Gazipur were used. The primary selection was made on the basis of their tolerance and susceptibility to water stages. The results revealed that all the studied parameters viz., plant height, canopy diameter, root length, root volume, no. of fruits per plant, fruit length, fruit diameter, individual fruit weight, no. of leaves per plant, leaf area per plant, fruit yield per plant, leaf dry weight, stem dry weight, root dry weight, fruit dry weight per plant, varied significantly among the accessions under different water treatments at different stages of growth. Out of four accessions, C-0271 and C-0277 were found as water stress tolerant and susceptible, respectively. Key Words: Water level; growth stage; chilli accessions DOI: 10.3329/bjar.v34i1.5764Bangladesh J. Agril. Res. 34(1) : 143-155, March 2009